2020
DOI: 10.1097/mnm.0000000000001257
|View full text |Cite
|
Sign up to set email alerts
|

Synergic role of preoperative 18F-fluorodeoxyglucose PET and MRI parameters in predicting histopathological features of endometrial cancer

Abstract: Background The aim of the present study is to explore the correlation between PET and MRI parameters of primary tumour and clinicopathological features and to determine their synergic predictive role in patients with endometrial cancer candidate to surgery. Methods Retrospective study including 27 patients with endometrial cancer and preoperative 18F-fluorodeoxyglucose (18F-FDG)-PET and MRI scan. The following parameters, calculated on the primary tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, very few studies have investigated the accuracy and predictive value of simultaneous 18F-FDG PET/MRI in the staging setting of endometrial cancer, so far. Volume index, TLG and SUVmax/ADCmean ratio derived from distinct MRI and PET scans predict myometrial invasion and lymph node involvement or disease recurrence [21,27,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, very few studies have investigated the accuracy and predictive value of simultaneous 18F-FDG PET/MRI in the staging setting of endometrial cancer, so far. Volume index, TLG and SUVmax/ADCmean ratio derived from distinct MRI and PET scans predict myometrial invasion and lymph node involvement or disease recurrence [21,27,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Median SUVmax, SUVmean40, MTV40 and TLG were respectively 21 MRI detected the primary tumor in all patients (100%) and pelvic lymph node involvement was found in 8 patients (patient based; 28%). Primary tumor median TTV, volume index and TVR were 9.47 cc (IQR 3.5 -42.65), 23.92 cc (IQR 7.66-98.48) and 19.46 cc (IQR 7.…”
Section: F-fdg Pet/mr Image Ndingsmentioning
confidence: 94%
See 1 more Smart Citation
“…The results showed that the accuracy and sensitivity of residual and new lesions in PHC patients detected by MRI was significantly higher than that by CECT (P<0.05). Mapelli et al ( 20 ) pointed out that the accuracy and sensitivity of CECT were 82.31% and 71.96%, respectively, which were significantly lower than the 93.68% and 93.29% of MRI, respectively. This demonstrated that MRI examination is more comprehensive and accurate in evaluating the activity of tumor lesions in patients postoperatively, and its accuracy and sensitivity in detecting residual and new lesions in patients after surgery were also higher.…”
Section: Discussionmentioning
confidence: 99%
“…18 Ffluoro-deoxyglucose ( 18 F-FDG) positron emission tomography (PET) has a well-established role in the preoperative staging of EC patients, and it is included in the clinical guidelines on EC management [24,25]. Precisely, 18 F-FDG is useful in providing a whole-body assessment of the disease, therefore identifying possible LN involvement and distant metastases [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%